The MedZEB Protocol: a Powerful Tool for Fostering Deep Renovation in the Mediterranean Area - Luca Laghi (AIDIC Servizi S.r.l., 2021)
The market uptake of deep energy retrofitting represents a significant challenge in the EU Mediterranean countries, due to specific bottlenecks which lead to a low level of trust. In order to meet these challenges, the H2020 HAPPEN Project has developed the MedZEB Protocol, a tool conceived for enhancing the quality management of the overall renovation process, and tailored for the residential sector of the Mediterranean Area. The Protocol is based on a holistic approach aimed at maximizing the added value generated by retrofitting interventions, as well as on standardized procedures which allow fostering a deeper integration among the actors involved, relying on higher technical expertise and enhancing the market transparency. The paper describes the main features of the MedZEB Protocol, its architecture, the indicators and the actors/procedures involved in each phase. The results of a feasibility analysis are also presented, which show the sustainability of the Protocol adoption, thus highlighting its potential role as a reference framework for fostering deep energy retrofitting in the Mediterranean area.